Inflation targeting and unemployment rate in Malaysia: The threshold regression approach - Taasim, Shairilizwan; Teruki, Neilson; Wong, Sing Yun; Pinjaman, Saizal (Enriched Publications, 2022)
Abstract: The first concern is a matter of theory the Phillips curve which show the trade-off relationship between the inflation and unemployment rates. Hence, this study aims to estimate threshold effects using the threshold autoregressive model proposed by Hansen (2000). In the context of Malaysia, we employed the monthly data from 2015 to 2022 to address the relationship between inflation and the unemployment rate. Specifically, we found difference with two perspectives on the relationship. The most interesting finding of this study is the higher inflation with existence of the Phillips curve in the short run. Therefore, a lower inflation rate results in higher unemployment rate relationship.